2014
DOI: 10.1007/s10900-014-9823-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neighborhood and Individual Characteristics on Pediatric Critical Illness

Abstract: The relationship between neighborhood/individual characteristics and pediatric intensive care unit (PICU) outcomes is largely unexplored. We hypothesized that individual- level racial/ethnic minority status and neighborhood-level low socioeconomic status and minority concentration would adversely affect children’s severity of illness on admission to the PICU. Retrospective analyses (1/1/2007–5/ 23/2011) of clinical, geographic, and demographic data were conducted at an academic, tertiary children’s hospital PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…Our findings are consistent with prior research showing that residing in an ethnic enclave is related to risk of disease [16,19], including several cancers [13,20-26]. The direction of our observed associations was anticipated based on our previous findings regarding HL incidence by nativity [13,14], which is one component of our neighborhood enclave index.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with prior research showing that residing in an ethnic enclave is related to risk of disease [16,19], including several cancers [13,20-26]. The direction of our observed associations was anticipated based on our previous findings regarding HL incidence by nativity [13,14], which is one component of our neighborhood enclave index.…”
Section: Discussionsupporting
confidence: 92%
“…[15,16,19,39-43]. Given established risk factors for HL, the observed association with ethnic enclave residence likely relates to relevant social community characteristics (e.g., education, family size [8], SES [4-6], household crowding [44]) and/or other environmental influences (e.g., smoking [45]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Locally, our group found that measures of poverty and housing quality were associated with a return to the hospital for children with asthma. 20,31 Also, a recent study by Epstein et al 32 showed that lower neighborhood income is associated with higher severity of illness on admission to the pediatric intensive care unit across diagnoses. Such findings are not surprising given the extensive literature on the influence of socioeconomic deprivation on a child’s physical health.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several other studies in the United States which found a link between neighborhood‐level SE disadvantages and morbidity and mortality independent of individual SE status 10, 11, 12. None of these studies, however, accounted for level of insurance coverage or cost‐sharing amount (eg, deductible amounts), which are important predictors of health care utilization and adverse health outcomes 13.…”
Section: Introductionmentioning
confidence: 97%